Nimodipine after aneurysmal subarachnoid hemorrhage: shortened treatment in an unselected patient cohort - Bryndís Baldvinsdóttir; Peo Wästberg; Björn M. Hansen; Erik Uvelius; Erik Kronvall (Brain and Spine)
Background: Nimodipine improves outcome after aneurysmal subarachnoid hemorrhage (aSAH) through mitigation of delayed cerebral ischemia (DCI). Most studies are based on a treatment duration of 21 days. At our institution, clinical practice is to administer nimodipine for 14 days, regardless of bleeding severity. Treatment is prolonged if signs or symptoms of DCI occurs. The present study aims to review this practice. Methods: A prospective cohort of aSAH patients was reviewed and relevant information regarding nimodipine treatment were retrospectively added to this database. Functional outcome was measured using Glasgow outcome scale extended (GOSE) one year after ictus and dichotomized into unfavorable and favorable outcome. Radiological outcome was defined by the occurrence of new cerebral infarctions on brain imaging later than 30 days post-ictus. Results: The study population comprised 164 patients, out of which 97 (59 %) received nimodipine for 14 days or less. Unfavorable outcome was noted in 27 % of patients and brain imaging found cerebral infarctions in 17 % of patients. Both outcome measures were similar to previously published studies. No readmissions or signs of DCI were seen after discontinuation of nimodipine. Conclusions: A shortened nimodipine treatment period in patients without DCI after aSAH could be feasible. This may reduce sleep deprivation of patients and more effective utilization of neurointensive care resources. A large, randomized study is required to answer the question whether a shorter treatment with nimodipine is adequate to give full benefit of the medication in patients without signs and symptoms of DCI.